2018
DOI: 10.21577/0103-5053.20180228
|View full text |Cite
|
Sign up to set email alerts
|

Metal Contents and Pb Isotopes in the Surface Seawater of the Gulf of Prigi, Indonesia: Detection of Anthropogenic and Natural Sources

Abstract: In order to investigate the anthropogenic and natural sources of metals in the Gulf of Prigi, Indonesia, it was analyzed their metal contents and Pb isotopes of surface seawater together with sediment, grouper fish, mosh, seaweed, soil, and sharp grass for protecting the environmental pollution of the study area. Samples were leached using a microwave digestion technique. Metal (Ca, Fe, Mn, Cu and Pb) concentrations and 206 Pb, 207 Pb and 208 Pb in the leached solutions were analyzed using inductively coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The adsorption process could be carried out using a membrane based on the natural materials, such as coral skeletons and beach sand obtained from Prigi Beach. Wijaya, et al (2020) reported that the anthropogenic activities that occur around the waters of Prigi Bay result in many inactive corals on the coast [4]. These inactive corals become coral skeleton waste known as coral skeletons [5]- [7], as well as analytical methods to identify heavy metal isotope ratios [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption process could be carried out using a membrane based on the natural materials, such as coral skeletons and beach sand obtained from Prigi Beach. Wijaya, et al (2020) reported that the anthropogenic activities that occur around the waters of Prigi Bay result in many inactive corals on the coast [4]. These inactive corals become coral skeleton waste known as coral skeletons [5]- [7], as well as analytical methods to identify heavy metal isotope ratios [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, from an ecological aspect, the exploitation of marine resources by modern fishers has had an impact on the destruction of marine and coastal ecosystems (Ahmed & Thompson, 2019). This occurs due to unlimited fishing activities with dangerous tools and materials; marine pollution by ship waste and oil spills; and industrialization in coastal areas causing large amounts of waste to enter the sea, such as cases of pollution in Jakarta bay (Azizi et al, 2021;Kunzmann et al, 2018), Malacca Strait (Robertua et al, 2019), metal pollution and Pb isotopes in seawater at the surface of Prigi Bay (Wijaya et al, 2019), pollution of plastic waste in the Coastal Water of Makassar City (Afdal et al, 2019), and various water pollution around other coastal cities (Sui et al, 2020). The exploitation of marine resources also negatively impacts the physical degradation of coastal ecosystems, such as damage to mangrove ecosystems, coral reefs, and coastal abrasion.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of heavy metals is naturally difficult to remove and finally accumulate in aquatic biota and sediments. Some researches used sediment, coral and marine biota to record heavy metals [1]- [3].…”
Section: Introductionmentioning
confidence: 99%